2012
DOI: 10.1590/s0365-05962012000600019
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic clues in the diagnosis of amelanotic and hypomelanotic malignant melanoma

Abstract: The clinical identification of amelanotic malignant melanoma (AMM) and hypomelanotic malignant melanoma (HMM) becomes difficult due to the lack of pigmentation and to the diverse clinical presentations. Dermoscopy is very useful in these cases, increasing the level of suspicion of malignancy. We report 4 cases of amelanotic malignant melanoma and hypomelanotic malignant melanoma with characteristic dermoscopic findings. Dermoscopy under polarized light demonstrates vascular polymorphism, globules and milky-red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In total, 62 articles were included in this systematic review, reporting on 433 melanoma cases. Of these articles, 30 reported on amelanotic melanoma (275 cases), 6 on animal-type or pigmented epithelioid melanocytoma (PEM) (7 cases), 4 on balloon cell melanoma (5 cases), 4 on desmoplastic melanoma (66 cases), 1 on follicular melanoma (1 case), 4 on nested melanoma (6 cases), 5 on nevoid melanoma (31 cases), 1 on primary dermal melanoma (1 case), 3 on spitzoid melanoma (28 cases), and 4 on verrucous melanoma (4 cases) . One study reported both amelanotic and spitzoid melanoma cases .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 62 articles were included in this systematic review, reporting on 433 melanoma cases. Of these articles, 30 reported on amelanotic melanoma (275 cases), 6 on animal-type or pigmented epithelioid melanocytoma (PEM) (7 cases), 4 on balloon cell melanoma (5 cases), 4 on desmoplastic melanoma (66 cases), 1 on follicular melanoma (1 case), 4 on nested melanoma (6 cases), 5 on nevoid melanoma (31 cases), 1 on primary dermal melanoma (1 case), 3 on spitzoid melanoma (28 cases), and 4 on verrucous melanoma (4 cases) . One study reported both amelanotic and spitzoid melanoma cases .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the superficial spreading melanoma (SSM) variant, only a few cases appear to be completely amelanotic on clinical and dermoscopic examination. By systematically searching the literature, we identified 30 studies reporting the clinical and dermoscopic features of 275 amelanotic SSMs . We found 8 additional amelanotic cases from our database, for a total of 283 SSMs.…”
Section: Resultsmentioning
confidence: 99%
“…Steglich et al stated that melanoma initially shows dotted vessels and that with greater thickness, vascular polymorphism increases, with hairpin and linear-irregular vessels associated with milky-red areas. Dotted vessels may be the only clue to suspect non-pigmented melanoma [ 36 ]. Similar to thin amelanotic melanomas on non-glabrous skin showing only dotted vessels under dermoscopy, VPRP may be an important alerting sign for early diagnosis of ALM.…”
Section: Discussionmentioning
confidence: 99%
“…The melanoma reported here was a hypopigmented superficial spreading melanoma (SSM) with a dominant nodule, which was notable because of its dominant structureless yellow color. In one series of four cases of AHM with dermatoscopic images, all cases had significant pink or red color and none had any yellow color [ 4 ]. Although this lesion fulfilled the definition of AHM, according to revised pattern analysis (RPA), the presence of any pigment should lead to a diagnostic analysis based on pigmented structures [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%